The Research on Teaching of Mathematical Understanding in China - Wang, Kai; Yang, Zezhong (American Journal of Education and Learning, 2018)
In mathematics teaching, understanding is the value embodiment of the whole mathematics classroom teaching. In recent years, some researchers have conducted extensive discussions on the basic problems of how to teach mathematical understanding from the aspects of theory and practice from different perspectives and have obtained many research results.In order to better carry out the teaching of mathematical understanding, this paper reviews the related literature from the aspects of classroom communication, teaching evaluation, teaching reflection, arrangement of teaching knowledge and materials, arrangement of teaching activities and design of teaching media, hoping to promote the future research and development of mathematical understanding teaching.